Spatial distribution of water quality in water bodies influenced by agricultural activities - Yustika, Rahmah Dewi; Sukarjo, Sukarjo; Dewi, Triyani; Yustiawati, Yustiawati; Handayani, Cicik Oktasari; Yanti, Delvi; Dariah, Ai (Brawijaya University, 2025)
Agriculture is a major contributor to non-point source pollution due to the intensive use of agrochemicals. This study examined the spatial distribution of pollutants from agricultural activities in the Sumani sub-catchment, West Sumatra, Indonesia, which drains into Lake Singkarak. Thirteen water quality parameters were measured, including electrical conductivity (EC), total suspended solids (TSS), total dissolved solids (TDS), dissolved oxygen (DO), sulfate, nitrate, calcium, sodium, total phosphorus (TP), potassium, magnesium, chlorpyrifos, and mancozeb. Results showed significant variation in water quality across the sampling sites. Downstream areas had higher levels of TSS, TDS, and major ions, mainly due to agricultural and urban activities. The lowest TSS levels were recorded at a site within the lake, likely due to sediment settling. River water generally met drinking water standards; however, TP and DO concentrations in the lake exceeded regulatory limits, potentially influenced by floating net cage aquaculture. Principal Component Analysis identified three main sources of pollution: agricultural activities (34.87%), combined agricultural and urban influences (20.15%), and soil erosion (12.15%). These findings highlight the need for better erosion control, sustainable farming practices, and consistent water quality monitoring. Further research is crucial to understand the long-term effects of agriculture on water resources and to develop strategies that reduce environmental impacts.